Factors associated with the transmission of soil-transmitted helminthiasis among schoolchildren - Isra Firmansyah; Sri Alemina Ginting; Munar Lubis; Iskandar Z Lubis; Syahril Pasaribu; Chairuddin P Lubis (Indonesian Pediatric Society Publishing House, 2016)
Background Soil-transmitted helminthiasis (STH) is an important public health problem in Indonesia. Objective To find out factors influencing the transmission of STH in two different communities in North Sumatera, Indonesia. Methods A cross sectional study was done on 96 primary school children in Suka village (located on a mountain area) and 96 pri- mary school children in Pantai Cermin village (a coastal area). Sub- jects were recruited by simple random sampling. Kato Katz and centrifuge floatation methods were used for stool and soil exami- nations, respectively. Data were collected by interviewing parents of children using a questionnaire and were analyzed using chi- square test by SPSS program version 11.0. Results There was no difference in the prevalence of STH in both villages (p>0.05). Parents' knowledge and economic status had significant relationships with the prevalence of STH in Suka vil- lage (p<0.05), but not in Pantai Cermin (p>0.05). In both villages, parents' education did not have a significant relation with STH, while there were significant relations between STH and hygiene, environment, or soil contamination by worm eggs (p<0.05). Conclusion There were significant relationships between hygiene, environment, or soil contamination and the prevalence of STH in the two villages.